2007
DOI: 10.1016/j.psyneuen.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal (+)-methamphetamine increases brain derived neurotrophic factor, but not nerve growth factor, during treatment and results in long-term spatial learning deficits

Abstract: SummaryIn this study, brain derived neurotrophic factor (BDNF) and nerve growth factor (NGF) were examined at five time points [postnatal day (P)11, 15, 20, 21, and 68 (the latter with or without behavioral testing)] during and after P11-20 (+)-methamphetamine (MA) (10 mg/ kg 4 × day) treatment. BDNF in MA-treated animals was elevated on P15 and P20 in the hippocampus but not in the hypothalamus and was unchanged on P11 and P21. On P68 (1 h after Morris water maze testing) MA-treated offspring showed a trend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
(71 reference statements)
5
23
1
Order By: Relevance
“…This is in line with data by Skelton et al [2007], who showed a regulation of NGF after neonatal methamphetamine exposure at P20 in the hippocampus. In adult rats, NGF expression was decreased only in the hippocampus, occipital cortex and hypothalamus after amphetamine injections, but no change in NGF levels was found in the frontal cortex [Angelucci et al, 2007].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with data by Skelton et al [2007], who showed a regulation of NGF after neonatal methamphetamine exposure at P20 in the hippocampus. In adult rats, NGF expression was decreased only in the hippocampus, occipital cortex and hypothalamus after amphetamine injections, but no change in NGF levels was found in the frontal cortex [Angelucci et al, 2007].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies in amphetamine-experienced animals, in which drug exposure (experimenter-delivered) significantly enhanced BDNF protein levels in the hippocampus (Skelton et al, 2007, Grace et al, 2008), but significantly extend the findings with methamphetamine self-administration, a paradigm that produces much lower levels of drug intake compared with high dose experimenter delivered paradigms. Upon release into the synaptic cleft, BDNF can bind to its receptor TrkB, localized at both pre- and postsynaptic sites of glutamatergic synapses in the hippocampus, and BDNF binding to TrkB induces receptor dimerization and phosphorylation at the autophosphorylation site Tyr-706 (Drake et al, 1999, Chao, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…In the context of addiction, cocaine exposure produces a widespread, but transient, induction of BDNF protein in the nucleus accumbens, prefrontal cortex, ventral tegmental area, and the central and basolateral nuclei of the amygdala (Grimm et al, 2003, Le Foll et al, 2005, Graham et al, 2007), whereas fewer studies have been conducted to examine BDNF protein levels after exposure to amphetamines. For example, BDNF protein expression in the hippocampus in enhanced in juvenile animals after forced administration of neurotoxic doses of amphetamines and the findings demonstrate that these changes in the neurotrophin may relate to the cognitive deficits in methamphetamine experienced animals (Skelton et al, 2007, Grace et al, 2008). In contrast to these studies using noncontingent methamphetamine injections, there are no published studies on the effect of methamphetamine self-administration on hippocampal BDNF levels, and therefore, was the focus of the current study.…”
Section: Introductionmentioning
confidence: 90%
“…A relationship between CORT and BDNF was also observed, which could explain the BDNF effects discovered in the MDMA-treated animals (Roskoden et al, 2004). Increases in BDNF have also been shown in MA-treated animals on P15 and P20 (Skelton et al, 2007). MDMA (10 mg/kg) exposure from P1 to P4 increased the cleavage of caspase-3, an apoptotic marker, in the rostral forebrain on P5, suggesting that MDMA may be inducing apoptosis in developing neurons (Meyer et al, 2004).…”
Section: Biochemistrymentioning
confidence: 71%